2015
DOI: 10.1080/10548408.2014.986012
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Taiwan Destination Brand Associations: From the Perspective of Mainland Chinese Tourists

Abstract: Grounded on the concept of brand associations by Keller and Associative NetworkTheory, this study examined Taiwan destination brand associations as perceived by Mainland Chinese tourists. The qualitative data were obtained through a survey using open-ended questions among package-group tourists from Mainland China to Taiwan in 2010. Data were coded and analyzed using qualitative and quantitative approaches. As a result, the three types and three dimensions of Taiwan destination brand associations were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In addition, the existing literature on national brands is mainly analyzed from the perspective of the uniqueness of national culture, brand image, brand association, etc. [ 66 , 67 , 68 ]. This paper, however, takes the emotional factor of collective nostalgia as an antecedent variable to explore its internal mechanism of influence on national brand consciousness, which not only enlarges the vision for the future study of consumer behavior theory and national brand theory, but also provides a reference for the development of nostalgic marketing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the existing literature on national brands is mainly analyzed from the perspective of the uniqueness of national culture, brand image, brand association, etc. [ 66 , 67 , 68 ]. This paper, however, takes the emotional factor of collective nostalgia as an antecedent variable to explore its internal mechanism of influence on national brand consciousness, which not only enlarges the vision for the future study of consumer behavior theory and national brand theory, but also provides a reference for the development of nostalgic marketing.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, this study applies the previous research findings to the field of marketing and concluded through empirical analysis that collective nostalgia has a positive impact on consumers' national brand consciousness. In addition, the existing literature on national brands is mainly analyzed from the perspective of the uniqueness of national culture, brand image, brand association, etc [66][67][68]…”
mentioning
confidence: 99%
“…The study notes that "face" is an important concept in understanding Chinese outbound travelers, and gift purchase and giving is a significant outbound tourist activity to maintain face and harmonious social relations for Chinese outbound tourists. To a lesser extent, Huang, Li, and Li (2015) examined the destination brand of Taiwan among mainland Chinese tourists, applying a cultural perspective implicitly.…”
Section: From Motivations To Cultural Value Explanationsmentioning
confidence: 99%
“…Their findings may help marketers craft Taiwan's unique destination features. Further, Huang and Li's (2015) brand association of Taiwan and Song and Hsu's (2013) study of Taiwan's destination image discussed Chinese tourists' perspectives of Taiwan's destination image. However, these studies have not examined the formation of international tourists' loyalty toward the country.…”
mentioning
confidence: 99%